2023
DOI: 10.1002/cssc.202202071
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Synthesis of Covalent Adaptable Network (CAN) Polyurethanes from Lignin with Editable Shape Memory Properties

Abstract: Here a new strategy of catalyst-free direct synthesis of covalent adaptable network polyurethanes (LPUs) from lignin with editable shape memory effect is reported. Using unmodified lignin, PEG, and isocyanate under the condition of the isocyanate index less than 1.0 (NCO/OH < 1.0), a variety of LPUs are obtained. When NCO/OH = 0.8, a stable cross-linked network can be formed (ex. the gel content of LPU50-0.8 was 98 � 0.3 %). The activation energy (E a ) value of LPUs is similar to that of polyhydroxyurethanes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Lignin has been also exploited in polyurethane networks with CAN properties. 118 characterized with excess hydroxyl groups that participated in the exchange reactions involving urethane bonds (Scheme 22). When lignin content was low (<40%), the modulus and tensile strength of thermosets decreased with the increase of the isocyanate index (NCO/OH).…”
Section: Vanillin-based Thermosets As An Inspiration For Can Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin has been also exploited in polyurethane networks with CAN properties. 118 characterized with excess hydroxyl groups that participated in the exchange reactions involving urethane bonds (Scheme 22). When lignin content was low (<40%), the modulus and tensile strength of thermosets decreased with the increase of the isocyanate index (NCO/OH).…”
Section: Vanillin-based Thermosets As An Inspiration For Can Designmentioning
confidence: 99%
“…Lignin has been also exploited in polyurethane networks with CAN properties . Specifically, EHL was treated with poly ethyleneglycol with a molecular weight of 2000 (PEG 2000) and hexamethylene­diisocyanate (HDI).…”
Section: Lignin Building Blocks-based Cansmentioning
confidence: 99%
“…Although those LPUs had excellent bond exchange characteristics and processibilities, their mechanical properties were poor with a maximum toughness of around 9.93 ± 0.11 MJ m −3 . [17] Zhang et al reported a fully bio-based vitrimer with a high lignin content and the bio-based vitrimer showed excellent shape memory and repairing properties at elevated temperatures. However, the bio-based vitrimer had tensile strength of only 12.9 ± 1.5 MPa, with an elongation value of 10.8 ± 1.0%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Moreover, due to the complex structure and undefined molecular weight, most lignin‐based CANs reported in the literature possessed low mechanical properties. In an earlier study, [ 17 ] we prepared lignin‐based polyurethanes (LPUs) containing dynamic bonds using unmodified enzymatic hydrolysis lignin as the raw material via a new strategy of utilizing a low isocyanate index (NCO/OH < 1.0). Although those LPUs had excellent bond exchange characteristics and processibilities, their mechanical properties were poor with a maximum toughness of around 9.93 ± 0.11 MJ m −3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation